Intersection of Traditional Religious Authority and New Authority in the Digital Space of Indonesia - Lubis, Nikmah (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
The emergence of new media, such as social media, has provided a space for religious communities or groups to create religious narratives or religious discourses in the digital realm. Religion is represented in a more contemporary manner, supported by advanced information technologies, packaged, and reproduced in a more modern style. Religious discourse in the digital space has thus made religious authority fluid and complex, no longer rigid and solely held by religious institutions. This condition has given rise to what is known as online authority. Online authority, in the early studies of digital religious authority, is considered by several scholars to potentially shift the existence and legitimacy of traditional authorities that have been in existence for a longer period. Traditional authority is deemed unable to adapt to digital practices. Through a literature review approach, this paper concludes that traditional and online authority are not separate entities; traditional authority can enter and exist in the online domain with packaging, styles, and innovations that align with digital practices. Traditional authority, with its strong legitimacy, is capable of presenting itself in the online domain, being repackaged and represented in ways or styles that are in line with contemporary and modern trends.